2001
DOI: 10.1002/1522-2683(200105)22:7<1436::aid-elps1436>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Michaelis-Menten analysis of bovine plasma amine oxidase by capillary electrophoresis using electrophoretically mediated microanalysis in a partially filled capillary

Abstract: A method for determining bovine plasma amine oxidase (PAO; EC 1.4.3.6) activity with benzylamine (Bz) as substrate is described. Electrophoretically mediated microanalysis (EMMA) combined with micellar electrokinetic capillary chromatography (MEKC) was used to perform an on-capillary enzymatic reaction and to separate the generated benzaldehyde from the other reaction products. The capillary was only partially filled with the separation solution, since the enzyme was unstable in the presence of the applied sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…For the EMMA procedure we performed the partial‐filling mode developed by Van Dyck et al . First, a plug (−50 mbar for 6 s) containing CYP1A1 supersomes was hydrodynamically injected into a fused‐silica capillary, followed by a plug (−50 mbar for 6 s) that contained the cofactor (NADPH) and the substrate (7‐EC), then another plug (−50 mbar for 6 s) of CYP1A1 supersomes was injected (sandwich mode).…”
Section: Methodsmentioning
confidence: 99%
“…For the EMMA procedure we performed the partial‐filling mode developed by Van Dyck et al . First, a plug (−50 mbar for 6 s) containing CYP1A1 supersomes was hydrodynamically injected into a fused‐silica capillary, followed by a plug (−50 mbar for 6 s) that contained the cofactor (NADPH) and the substrate (7‐EC), then another plug (−50 mbar for 6 s) of CYP1A1 supersomes was injected (sandwich mode).…”
Section: Methodsmentioning
confidence: 99%
“…There is a paper reported that main phenolic acids and flavonoids in tomato were separated and determined simultaneously using MEKC. Sigrid Van et al achieved on‐line detection of the activity of bovine plasma amine oxidase. CZE was applied at early stage of the study, which is not able to separate benzylamine from other substrates.…”
Section: Screening Active Compounds Using Cementioning
confidence: 99%
“…After applying a certain voltage, the plugs will overlap each other and thus the incubation is initialized. If, at this stage, the voltage is turned off, the reaction product is accumulated, which is called ‘zero potential amplification’ .…”
Section: On‐line Enzyme Reaction Studiesmentioning
confidence: 99%
“…When the enzymatic reaction is not compatible with the background electrolyte (BGE), the plugs of enzyme and substrate can be separated from the BGE by injecting plugs of incubation buffer in between. This method is named ‘partial filling’ . In a study by Farcaş et al.…”
Section: On‐line Enzyme Reaction Studiesmentioning
confidence: 99%